5(n-7)-(3-4n)=8n

Simple and best practice solution for 5(n-7)-(3-4n)=8n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(n-7)-(3-4n)=8n equation:


Simplifying
5(n + -7) + -1(3 + -4n) = 8n

Reorder the terms:
5(-7 + n) + -1(3 + -4n) = 8n
(-7 * 5 + n * 5) + -1(3 + -4n) = 8n
(-35 + 5n) + -1(3 + -4n) = 8n
-35 + 5n + (3 * -1 + -4n * -1) = 8n
-35 + 5n + (-3 + 4n) = 8n

Reorder the terms:
-35 + -3 + 5n + 4n = 8n

Combine like terms: -35 + -3 = -38
-38 + 5n + 4n = 8n

Combine like terms: 5n + 4n = 9n
-38 + 9n = 8n

Solving
-38 + 9n = 8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-8n' to each side of the equation.
-38 + 9n + -8n = 8n + -8n

Combine like terms: 9n + -8n = 1n
-38 + 1n = 8n + -8n

Combine like terms: 8n + -8n = 0
-38 + 1n = 0

Add '38' to each side of the equation.
-38 + 38 + 1n = 0 + 38

Combine like terms: -38 + 38 = 0
0 + 1n = 0 + 38
1n = 0 + 38

Combine like terms: 0 + 38 = 38
1n = 38

Divide each side by '1'.
n = 38

Simplifying
n = 38

See similar equations:

| -2x^3=-128 | | 25-(-41)= | | x^2(x^2)-16(x^2-1)=0 | | -29-6x=-5(-5x+1)-7x | | Sinx=3 | | 2b+58b=35 | | -21+5+-9=3(t-4)-5 | | 71=6(4n-8)-7n | | 2(x-5)=3(x-1) | | s+6=78 | | 2x+3y-5x+5y= | | 5(1+6a)=-39+8a | | 2+2v=-2 | | 2z^3+9z^2=5z | | 5b-16-8n=-10 | | 7(y+1)=49 | | K=17 | | X+3=-32 | | 15-f=-23 | | 4-5(x+3)=25 | | -22+7r=6(r-4) | | 3x+7+6x+11=90 | | 4x+1=11x | | -2(5y+5)=4 | | 3*x=10 | | 8+16=-3(5x-8) | | 9(6x-5)=279 | | 22x-16x+12=-15+3x+12+6x | | 5x-9=13-x | | 7=20 | | 120*24= | | -30+5n=4+4(1+6n) |

Equations solver categories